The Influence of Accounting Bookkeeping, Cash Management, and Working Capital on the Performance of Grape MSMEs in Pejarakan Village, Gerokgak District - Komang Sekarini; Nyoman Ayu Wulan Trisna Dewi (INVEST : Jurnal Inovasi Bisnis dan Akuntansi, 2025)
This study aims to analyze the influence of accounting records, cash management, and working capital on the performance of grape SMEs in Pejarakan Village, Gerokgak District. This research is based on the important role of grape SMEs as a local economic sector facing challenges in financial management and capital optimization. This study uses a quantitative approach with data collection techniques through the distribution of questionnaires to wine SME actors. The population in this study is all wine SMEs in Pejarakan Village, totaling 50 units, which were also used as research samples using a saturated sampling technique (census), so that the research results cover all wine business actors in the area. Data analysis was conducted using multiple linear regression to test the influence of independent variables on dependent variables. The results of the study indicate that accounting records have a positive and significant effect on SME performance. Cash management was also found to have a positive and significant effect. Similarly, business capital has a positive and significant effect on performance.